What Does the Long-lived Nestor’s Cup Hold in Store? Remarks on the Reception of the Theme in Iconography and Literature - Milewska-Waźbińska, Barbara (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The paper studies selected aspects of the reception of Homeric theme of Nestor’s cup in the early modern times, both in emblematics and in literary worksThe longevity of king of Pylos and his oratorical skills were often alluded to in the Greek and Latin literature. As it turns out, the interpretation of the cup’s adornments included in Athenaeus’ Banquet of the Learned was widely discussed in the early modern times. This interpretation contributed both to the study of emblematics and literary works. The Homeric theme left its indelible mark also on the Old Polish literature, as in the funeral oration in honor of Bishop of Cracow Jakub Zadzik entitled Nestor Sarmaticus written by Jan Cynerski-Rachtamowicz.